Evaluasi Kinerja Penyedia Jasa pada Pekerjaan Preservasi Jalan Nasional dengan Metode Ahp: Ruas Jalan Simpang Kawat – Aek Kanopan -Rantau Prapat - BTS. Provinsi Riau - Riski Anugrah; Ahmad Perwira Mulia Tarigan; Gina Cynthia Raphita Hasibuan (Syntax Idea, 2022)
Road preservation activities have an important role in maintaining road conditions so that they continue to function in serving traffic so that they can extend the service life of the road and ensure traffic safety. One of the road preservation activities that affect the success of the work is the capacity and capability of the service provider. The Service Provider as one of the procurement actors is also an important element that must be considered and will determine and influence the success of project governance. This study attempts to evaluate the performance of service providers on road preservation work based on road performance indicators using the Analytic Hierarchy Process (AHP) method. Service provider performance criteria will be identified as Road Performance Indicators (IKJ), Past Performance (KT), Safety Performance (KK), Financial Stability (SF), and Technical Resource Performance (KSDT). The weight values ​​from the results of the AHP method analysis for each criterion are: IKJ (0.289), KT (0.122), KK (0.203), SF (0.135), and KSDT (0.251). The performance of the preservation work service provider gets a performance score of 2,868 with a good predicate (2 to 3).